Cost-effectiveness analysis of durvalumab with chemotherapy and maintenance durvalumab with or without olaparib for advanced endometrial cancer - Jiahao Zhang; Jianying Lei; Caicong You; Wu Fu; Bin Zheng; Hongfu Cai; Maobai Liu; Na Li (Scientific Reports)
Abstract This study evaluates the cost-effectiveness of adding durvalumab to chemotherapy, with subsequent maintenance either with olaparib (DOCT) or without olaparib (DCT), versus chemotherapy alone (CT) as a first-line treatment for advanced endometrial cancer (EC) in the United States, stratified by mismatch repair deficiency (dMMR) and proficiency (pMMR). A Markov model based on DUO-E Phase III trial data simulated disease progression and outcomes. Total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICER) were evaluated. Sensitivity analysis assessed model robustness. For dMMR EC, costs (QALYs) were $1,204,763.33 (5.49), $590,732.13 (4.61), and $1,495,528.15 (3.68) for DOCT, DCT, and CT, respectively, with ICER of $584,140.94/QALYs (DOCT vs. CT) and $476,946.43/QALYs (DCT vs. CT). For pMMR EC, costs (QALYs) were $421,126.70 (3.00), $400,470.92 (2.45), and $133,424.52 (1.69), with ICER of $219,601.20/QALYs (DOCT vs. CT) and $351,777.86/QALYs (DCT vs. CT). In the overall population, costs (QALYs) were $607,921.80 (3.89), $417,637.19 (2.82), and $141,594.38 (2.16), with ICER of $269,195.01/QALYs (DOCT vs. CT) and $416,098.68/QALYs (DCT vs. CT). From a U.S. payer perspective, DOCT and DCT regimens are not cost-effective compared to CT for advanced or recurrent EC, including dMMR and pMMR subgroups, at a $150,000/QALY threshold.